Vietnam's updated Nationally Determined Contributions to the Paris Agreement, including new targets in agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Vietnam has increased the unconditional and conditional targets for greenhouse gas (GHG) mitigation in agriculture in its updated Nationally determined contributions (NDC) to 6.8MtCO2eq and 25.8MtCO2eq respectively (the previous targets were 6.42MtCO2eq and 10.21MtCO2eq respectively), based on CGIAR contributions on climate-smart rice production.